1999
DOI: 10.1093/toxsci/48.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic considerations of dexamethasone-induced developmental toxicity in rats

Abstract: Dexamethasone (DEX) has been shown to elicit growth stunting and cleft palate in rat fetuses. This investigation characterized DEX dosimetry as various pharmacokinetic parameters and evaluated their impact on developmental toxicity endpoints. DEX pharmacokinetics was evaluated as a single dose on either gestation day (GD) 9 or 14, as well as on GD 14 after multiple daily dosing from GD 9 to GD 14. An additional set of pregnant rats was dosed with DEX on GD 9 through GD 14, pharmacokinetic evaluation was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The effect of dexamethasone was transient lapsing after 4 h of treatment. This relatively short-lasting effect as compared to longer biological activity [45] and terminal half-life [46] reported in rats might be due to species differences in dexamethasone pharmacokinetics [46]. Besides its established anti-inflammatory properties, dexamethasone anticonvulsant effect may be mediated by its ability to reverse the increased serum corticosterone concentrations, which are elicited by elevated IL-1β brain levels via activation of the hypothalamic-pituitary adrenal axis (HPA) axis [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of dexamethasone was transient lapsing after 4 h of treatment. This relatively short-lasting effect as compared to longer biological activity [45] and terminal half-life [46] reported in rats might be due to species differences in dexamethasone pharmacokinetics [46]. Besides its established anti-inflammatory properties, dexamethasone anticonvulsant effect may be mediated by its ability to reverse the increased serum corticosterone concentrations, which are elicited by elevated IL-1β brain levels via activation of the hypothalamic-pituitary adrenal axis (HPA) axis [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…We found that a conventional two-compartment model with a zero-order absorption process best described the pharmacokinetics of DEX in our study. Both onecompartment [33,34] and two-compartment models [35] have been found to best describe DEX plasma concentration profiles [34] . The first-order absorption of DEX has been reported previously [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the persistent suppression in rats was not due to insufficient exposure compared with the concentrations used in cell culture. It was reported that rats dosed at 0.8 mg/kg produced a C max of 682 ng/ml in the blood, equivalent to ~1.7 μM (Hansen et al, 1999). Based on this estimation, a single ip injection of 50 mg/kg would produce a blood concentration of ~62.5 μM.…”
Section: Discussionmentioning
confidence: 99%